The nucleus: a highly organized but dynamic structure. - Gonzalez-Melendi, P; Beven, A; Boudonck, K; Abranches, R; Wells, B; Dolan, L; Shaw, P (2000)
The nucleus in plants and animals is a highly structured organelle containing several well-defined subregions or suborganelles. These include the nucleolus, interphase chromosome territories and coiled bodies. We have visualized transcription sites in plants at both light- and electron-microscopy level by the incorporation of BrUTP. In the nucleolus many dispersed foci are revealed within the dense fibrillar component, each of which probably corresponds to a single gene copy. In the nucleoplasm there are also many dispersed foci of transcription, but not enough to correspond to one site per transcribed gene. We have shown that in wheat, and probably many other plant species, interphase chromosome territories are organized in a very regular way, with all the chromosomes in the Rabl configuration, all the centromeres clustered at the nuclear membrane and all the telomeres located at the nuclear membrane on the opposite side of the nucleus. However, despite this regular, polarized structure, there is no sign of polarization of transcription sites, or of any preferred location for them with respect to chromosome territorial boundaries. The nucleus is also highly dynamic. As an example, we have shown by the use of a green fluorescent protein fusion to the spliceosomal protein U2B" that coiled bodies move and coalesce within the nucleus, and may act as transport structures within the nucleus and nucleolus.